Muslim minorities in the west: between fiqh of minorities and integration - Taha, Dina M. (AUC Knowledge Fountain, 2012)
Fiqh of minorities is a specific framework/perspective of the general Fiqh that looks with one eye at the objectives and principles of SharÃ®â a, and the other eye to consider the reality of Muslim minorities in cases that will, usually, only arise in the situation where Muslims constitute a minority. Fiqh of minority is, arguably, based on the premises that Muslim existence in non-Muslim communities, should promote a civilizational dialogue between the Islamic culture and other cultures. This paper argues that Fiqh of minorities' scholars attempt to provide legal opinions and solutions for Muslim minorities in the West in order for them to fulfill their role as both good Muslims and good citizens, i.e. positive integration as they define it. The paper asks whether the cultural background of the scholarâ Western/non-Westernâ impacts the nature of these solutions. The paper argues that Fiqh of minorities can provide two types of solutions a long-term one, for a permanent Muslim presence in the West, and a Short-termâ exceptionalâ one, for a temporary presence. The first suggests that we are dealing with full citizens and members of the society who happen to be Muslims in religion, while the second assumes that Muslims' natural and ultimate residence is in a Muslim majority country. Both types of solutions are reflected on the nature of the compromise Fiqh of minorities' scholars, who in turn are affected by their own cultural backgrounds, provide to solve â the good Muslim, Good citizen equationâ â i.e. whether they are perceived as â Western Muslims" or â a Muslim minority in the West".